Potential use of repetitive transcranial magnetic stimulation in treating pediatric avoidant/restrictive food intake disorder: a case report - Wang, Ru; Wu, Shiling; Fu, Cuiyuan; Li, Kun (Frontiers in Psychology, 2025)
BackgroundAvoidant/Restrictive Food Intake Disorder (ARFID) is a heterogeneous eating disorder that typically manifests during adolescence, potentially leading to various health issues, such as malnutrition, developmental delays, and psychological disturbances. Currently, the management of ARFID is multidisciplinary, involving dietary modifications, pharmacological treatments, and psychotherapy, but no standardized treatment protocol exists. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive brain stimulation technique, has shown promise in treating various psychiatric disorders. However, its application in ARFID treatment remains under-explored.Case ReportThis case study presents a 5-year-old boy diagnosed with ARFID and severe malnutrition, who underwent adjunctive low-frequency rTMS therapy. The patient received 1 Hz rTMS stimulation targeting the right dorsolateral prefrontal cortex, with a single session consisting of 1,200 pulses administered once daily for 11 consecutive days. After 11 sessions of TMS treatment, when evaluated using the clinical global impression-improvement scale, the patient was scored 2 points, indicating a moderate improvement in symptoms. Twelve days after hospital admission, the patient exhibited significant improvements in emotional status and eating behavior, and no adverse reactions were observed. Subsequently, the patient was discharged from the hospital. Within two months post-discharge, the patient’s body weight was restored and remained stable throughout the one-year follow-up period.ConclusionThis case report offers preliminary evidence regarding the application of low-frequency rTMS directed at the right dorsolateral prefrontal cortex as a potential therapeutic approach for childhood ARFID. Our findings add to the burgeoning body of literature on rTMS therapy for ARFID and lend support to the effectiveness and safety of low-frequency rTMS as a treatment modality for childhood ARFID.